PERILAKU PACARAN SISWA DITINJAU DARI TEMPAT TINGGAL DI SMK X PEKANBARU - Suryani, Eva Reksa; Saam, Zulfan; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: dating behavior is an activity between men and women based on feelings of pleasure, love, affection, attention with a touch of feeling for the purpose, namely finding ways that are more familiar with the stages of shooting and acceptance (commitment). In addition, courtship is also considered as one way to find a match between couples to display households and families. For some teenagers this is considered normal because it is motivated by a mere sense of attraction. The indicators that will be examined on dating behavior according to Santrock (2003) are keepsake (ie), constant association (maintaining relationships), trust (giving trust), creative expression (creative expression), touching (reaching), kissing (kiss) . This study aims to determine the general dating behavior of students, ranging from students who live with family and students who live in boarding houses. The subjects of this study were thirty-four-year-old students who were dating from the place of residence (with their families and boarding houses) using purposive sampling. This research uses descriptive method with a quantitative approach. In this study the instrument used was a questionnaire. To analyze data using percentages. The results showed that; 1) Behavior of dating students doing activities giving surprises and thanking their partners. 2) Behavior of dating students who live with family doing creative expression activities, similar to students living in boarding houses.Keywords: Dating behavior, residence